Peran Sector Pertanian Terhadap Pertumbuhan Ekonomi Serta Dampaknya Pada Kemiskinan dan Kesejahteraan Masyarakat 2018-2023 - Haryono, Sugeng; Nurlaela; Muhammad Syahiddin (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
The aim of this research is to find out how much influence the agricultural sector has on economic growth and how big its impact is on poverty and social welfare in Indonesia. research method, this research takes the population from panel data on economic variables, namely the agricultural sector, economic growth data, poverty data and community welfare in Indonesia. And a sample of part of the population, namely data from the 10 largest agricultural producing provinces, and over the last 6 year period from 2018-2023. The sampling technique or sampling is non-probability sampling with quota sampling type, data calculation using the eviews tool 10. The results of the research, the agricultural sector shows a significant and positive influence from the results of numerical data and surveys from social media, that the agricultural sector is leading sectors and those that can help GRDP in Indonesia. Because the industrial sector helps the food processing industry. And with the influence of the agricultural sector on economic growth, it has an impact on decreasing and increasing poverty and social welfare, because many people still have hope in the agricultural sector, such as areas where there is still a lot of agricultural land such as rice fields.